Respuesta :
Answer:
[tex]g(x)=(x-3)(x+2)(x-2)[/tex]
Step-by-step explanation:
Given:
- Polynomial: g(x) = x³ - 3x² - 4x + 12
- Zero: 3
Factor Theorem
If f(x) is a polynomial, and f(a) = 0, then (x – a) is a factor of f(x).
Therefore, if 3 is a zero of g(x), then g(3) = 0 and so (x - 3) is a factor of g(x):
[tex]\implies g(x)=(x-3)(ax^2+bx+c)[/tex]
As the leading coefficient of g(x) is one, a = 1:
[tex]\implies g(x)=(x-3)(x^2+bx+c)[/tex]
As the constant of g(x) is 12, c = 12 ÷ -3 = -4:
[tex]\implies g(x)=(x-3)(x^2+bx-4)[/tex]
Expand:
[tex]\implies g(x)=x^3+bx^2-4x-3x^2-3bx+12[/tex]
[tex]\implies g(x)=x^3+(b-3)x^2-(4+3b)x+12[/tex]
Compare the coefficients of the terms in x² to find b:
[tex]-3x^2=(b-3)x^2 \implies b=0[/tex]
Therefore:
[tex]\implies g(x)=(x-3)(x^2-4)[/tex]
[tex]\boxed{\begin{minipage}{5 cm}\underline{Difference of Two Squares}\\\\$a^2-b^2=(a+b)(a-b)\\ \end{minipage}}[/tex]
To factor (x² - 4), rewrite as (x² - 2²) and apply the difference of two squares:
[tex]\implies g(x)=(x-3)(x+2)(x-2)[/tex]
Therefore, the function g(x) as a product of linear factors is:
- [tex]g(x)=(x-3)(x+2)(x-2)[/tex]
Check by expanding the factored function:
[tex]\implies g(x)=(x-3)(x+2)(x-2)[/tex]
[tex]\implies g(x)=(x^2-x-6)(x-2)[/tex]
[tex]\implies g(x)=x^3-2x^2-x^2+2x-6x+12[/tex]
[tex]\implies g(x)=x^3-3x^2-4x+12[/tex]